A study of bubbly flow using resistivity probes in a novel configuration - K., Sanaullah; S.H., Zaidi; J.H., Hills (Elsevier, 2001)
Among the various methods used for bubbly flow measurements, the double-sensor resistivity probe has been found very effective. Resistivity probes in horizontal and vertical configurations suffer from problems of stability and hydrodynamic resistance, respectively. Better results can be obtained by using an inclined probe. The impact of inclination on the measured bubble size, bubble frequency, local void fraction and interfacial area density concentration has been investigated in this study. For this purpose data from two inclined probes (110 and 145) has been compared with that from a vertical probe. All three probes were used in a 150mm diameter flow column. The flow conditions were chosen to develop a discrete two-phase bubbly flow. It was found that probe inclination could have a great effect on the fraction of bubbles captured by both probes, but that the effect on the various measured parameters was less. Among the three probes, the 110 inclined probe gave the best performance.